Climate Risk & Vulnerability (CR&V) assessment for climate services: Inland fisheries production and value chain - Lower Mekong Basin, Cambodia - Kong, Heng; Soksophors, Yim; Raksa, Sok; Giles, James; Swaans, Cornelis (2023)
As part of the CGIAR Initiative on Asian Mega Deltas, a scoping study was recently completed to prioritize key delta-oriented production systems and value chains for the Lower Mekong Basin (LMB) in Cambodia (Gonsalves et al, 2022). Rice, vegetables, and inland fisheries were selected based on a set of criteria including production, economic and nutritional value, climate change impact, and potential benefit of climate services with specific attention for the role of women and smallholders. To better understand the climate service needs of selected production systems and value chains in the Lower Mekong Basin, an additional value chain climate risk and vulnerability assessment was made. This report focuses on inland fishery production and value chain.